Spectroscopy studies of 4H-SiC - Oliveira, A.C. de (2003)
Calculations of the total dielectric functions and the optical bandgap energy (OBGE) of 4HSiC were performed by the full-potential linear muffin-tin-orbital method. The results are compared to spectroscopic ellipsometry dielectric measurements agreeing closely over in a wide range of energies. The obtained theoretical value of the (OBGE) agrees very closely with the measured ones obtained by transmission and photoacoustic spectroscopies at room temperature performed on 470 µm thick wafer and a 25 µm thick homoepitaxial layer of 4H-SiC samples grown (n-type, Siface) by hot wall CVD.